2008
DOI: 10.1111/j.1469-1809.2007.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Close Genetic Relationship Between Semitic‐speaking and Indo‐European‐speaking Groups in Iran

Abstract: SummaryAs part of a continuing investigation of the extent to which the genetic and linguistic relationships of populations are correlated, we analyzed mtDNA HV1 sequences, eleven Y chromosome bi-allelic markers, and 9 Y-STR loci in two neighboring groups from the southwest of Iran who speak languages belonging to different families: Indo-Europeanspeaking Bakhtiari, and Semitic-speaking Arabs. Both mtDNA and the Y chromosome, showed a close relatedness of these groups with each other and with neighboring geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
5
23
1
Order By: Relevance
“…mtDNA diversity encompassing most of the examined Iranian ethnic groups at both HVS-I and coding sequences lies within the range previously observed in populations speaking Indo-European or Semitic languages [11,19,20,[38][39][40] . Moreover, the bulk of the Iranian mtDNA variability roughly occupies an intermediate position between Western and Central Asian populations, with a negligible internal structure.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…mtDNA diversity encompassing most of the examined Iranian ethnic groups at both HVS-I and coding sequences lies within the range previously observed in populations speaking Indo-European or Semitic languages [11,19,20,[38][39][40] . Moreover, the bulk of the Iranian mtDNA variability roughly occupies an intermediate position between Western and Central Asian populations, with a negligible internal structure.…”
Section: Discussionmentioning
confidence: 66%
“…Reduced levels of mtDNA variability at binary and hypervariable markers are instead found for a few groups, such as Zoroastrians, Jews, Qashqaees, Lurs from Yasouj and Balochis who showed haplotype diversity values which fell outside the lower bound of previously investigated populations speaking Indo-European and Semitic languages from the South Caucasus, Middle East, West Asia and North Africa [11,19,20,[38][39][40] . Moreover, the Baloch sample coupled low HVS-I diversity with a heterogeneous haplogroup composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15] These studies were mostly based on sequences of the first hypervariable segment of the noncoding mtDNA control region (HV1) and Y chromosome binary marker variation in various groups from this region. mtDNA studies reveal a high level of diversity, exceeding that within all of Europe and only slightly lower than West Asian mtDNA diversity, which might indicate an old age of human populations from this region.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, based on both Ychromosome and mtDNA analyses, found little to no differences in ethnic groups (Indo-European speakers versus Semitic speakers) residing in close geographical proximity within Iran. 16 Furthermore, another mtDNA investigation led to the conclusion that two IndoIranian-speaking Talysh groups from Iran and Azerbaijan, that claim a common ancestry, were genetically similar. 17 In the same study, however, Y-chromosomal marker composition was shown to differ considerably between the Iranian and Azerbaijani Talysh, with the Azerbaijan Talysh more closely resembling the Azerbaijan neighbors than its Iranian counterpart.…”
Section: Introductionmentioning
confidence: 99%